Comparative analysis of pigment contents, phytochemical constituents, and antioxidant properties of selected plants in the Philippines - Kim Mariel S. Casuga; Lexter R. Natividad (International Research Journal of Science, Technology, Education, and Management)
During the pandemic, people turned to cultivating ornamental plants in their gardens. One of the trending plants is Mayana (Coleus blumei) for its leaves are pleasing to the eyes. Katuray (Sesbania grandiflora) and Sweet Potato Tops (Ipomoeas batatas), on the other hand, can be found everywhere in the different localities in the Philippines. This study aimed to trace the presence of different phytochemical constituents of Mayana, Katuray, and sweet potato tops. The presence of phytochemical constituents in Ipomoea batatas gave its property of anti-inflammatory, anti-bacterial, anti-fungal, and many more. In addition, results showed the presence of pigments in three plants such as carotenoid and chlorophyll content in the three plant samples. Further, the antioxidant properties were also identified. Analysis of Variance (ANOVA) results showed that there is a significant difference among the three plants at a 5% level of significance in terms of total carotenoid content. Furthermore, statistical analysis showed that there is a significant difference in the chlorophyll a and b in Ipomoea batatas, however, the post hoc test revealed that Coleus blumei and Sesbania grandiflora have no significant difference in their chlorophyll content. Meanwhile, thin-layer chromatographic analysis revealed that Ipomoea batatas has the greatest number of spots of all plant samples. Analysis of the total phenolics and antioxidant activity exhibited that Ipomoea batatas has the least quantitative result which means that it is the most potent among the three plant samples. This study therefore concluded that Ipomoea batatas can be formulated as a drug or supplement due to its antioxidant properties. The remarkable presence of different phytochemical constituents can give rise to new pharmaceutical products in the market.